2017
DOI: 10.1177/1358863x16681486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DPP-4 inhibition on acute and chronic endothelial function in humans with type 2 diabetes on background metformin therapy

Abstract: Cell culture and animal work indicate that dipeptidyl peptidase-4 (DPP-4) inhibition may exert cardiovascular benefits through favorable effects on the vascular endothelium. Prior human studies evaluating DPP-4 inhibition have shown conflicting results that may in part be related to heterogeneity of background anti-diabetes therapies. No study has evaluated the acute response of the vasculature to DPP-4 inhibition in humans. We recruited 38 patients with type 2 diabetes on stable background metformin therapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…The apparent effect of linagliptin to improve endothelial function, by a mechanism that is independent of any action on glucose concentration, is supported by observations that linagliptin treatment improves impaired endothelial function in mice with elevated lipid levels or where endothelium-dependent relaxation was impaired by sodium arsenite-induced oxidative stress 6. These findings are consistent with observations in diabetic patients, where DPP-4 inhibitors appear to improve endothelium-dependent relaxation in terms of increased flow-mediated dilatation of the brachial artery although it should be noted that not all studies with DPP-4 inhibitors have confirmed this effect 79…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The apparent effect of linagliptin to improve endothelial function, by a mechanism that is independent of any action on glucose concentration, is supported by observations that linagliptin treatment improves impaired endothelial function in mice with elevated lipid levels or where endothelium-dependent relaxation was impaired by sodium arsenite-induced oxidative stress 6. These findings are consistent with observations in diabetic patients, where DPP-4 inhibitors appear to improve endothelium-dependent relaxation in terms of increased flow-mediated dilatation of the brachial artery although it should be noted that not all studies with DPP-4 inhibitors have confirmed this effect 79…”
Section: Introductionsupporting
confidence: 80%
“…Treatment with linagliptin alone was reported not to affect FMD despite in one report being associated with improvements in microvascular function that were independent of any changes in glucose regulation 10. There are also reports in patients with type 2 diabetes where sitagliptin had no effect on FMD,7 and in another case even caused a deterioration in endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 is a metabolic regulator that also affects nutrient preference in humans and may be used to treat metabolic diseases [64132133134]. DPP4 is increased in islets of T2DM patients and DDP4 inhibitor-based therapies have had moderate success in reducing glucose intolerance and insulin resistance [135], while GLP-1 receptor agonists have shown promise for the management of T2DM and reducing weight [136].…”
Section: Bile Acid-based Therapy For Diabetesmentioning
confidence: 99%
“…Кроме того, на фоне приема ингибиторов ДПП-4 отмечалось уменьшение количества веществ клеточной адгезии -растворимой молекулы межклеточной адгезии 1 и Е-селектина [66]. Тем не менее протективный эффект ингибиторов ДПП-4 в отношении эндотелия сосудов подтвержден не во всех исследованиях [67][68][69]. Сообщалось также о негативном влиянии препаратов на эндотелиальную функцию [70].…”
Section: общая характеристика ингибиторов дипептидилпептидазыunclassified